The Level of Understanding of Several Syariah-Related Issues among Flood Victims in Flood Evacuation Centres in Malaysia - Muhammad Adib Samsudin; Mohammad Zaini Yahaya; Ahmad Munawar Ismail; Irwan Mohd Subri; Che Maryam Ahmad; Zainab Ismail; Rosmawati Mohamad Rasit; Illiyin Samsudin (Human Resource Management Academic Research Society, 2024)
Indexed by ERA